GREATER SOUTH ASIA— MERICA’S NEW REGIONAL APPROACH TO CENTRAL AND SOUTH ASIA: OW IT IS DEVELOPING AND WHAT PROMPTED IT - IAZMURADOV, Atajan (CENTRAL ASIA AND THE CAUCASUS, 2006)
Late in 2005 the United States opened a new page in its relationship with Central Asia as a region. Until that time the U.S. Administration still looked at it as a region in its own right, closely connected with the CIS and consisting of five post-Soviet states: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. Today the U.S. State Department is practicing a new approach based on an absolutely novel idea about regional division. Central Asia and South Asia form a single region, which I will call here Greater South Asia.In this article I have undertaken the task of tracing the evolution of this approach, starting from the moment of its official recognition. I shall also analyze the Greater Central Asia project of the Central Asia-Caucasus Institute of the Paul H. Nitze School of Advanced International Studies at the Johns Hopkins University, which the U.S. Administration adopted as the cornerstone of its new conception. I shall compare the projects of the U.S. Administration and the Central AsiaCaucasus Institute to arrive at certain conclusions.I shall investigate Central Asia’s new importance for the United States created by the new regional approaches. In addition, I shall analyze what prompted this approach (on which the Greater South Asia project rests) in the first place, as well as the aims the U.S. wants to achieve through the project.